Adults Living With a Retro-auricular Left Ventricular Assist Device as Destination Therapy: An Interpretive Description. Issue 6 (November 2020) - Luciani, Michela; Trenta, Alessia Martina; Jack, Susan Michelle; Moro, Massimo; Patella, Sara; Di Mauro, Stefania; Ausili, Davide
Abstract : Background: Increasingly, there is a trend toward the use of left ventricular assist devices (LVADs) for treating advanced heart failure, as both bridge-to-transplant therapy and destination therapy. Living with an LVAD profoundly influences patients' lives. Only a few study authors investigated the experience of people with abdominal LVADs, and nothing is known about the unique experience of those with retro-auricular LVADs. Objective: The aim of this study was to explore and describe experiences and lifestyle adjustments in adults with retro-auricular LVADs implanted as destination therapy. Methods: Interpretive description methodology was used to explore the experiences of a purposeful sample of 10 individuals with retro-auricular LVADs implanted as destination therapy. Data were collected using in-depth semistructured interviews. Data collection and analysis were simultaneous. Triangulation, journaling, and the "thoughtful clinician test" were used to increase trustworthiness of the findings. Results: Three primary themes describing the experience of people with retro-auricular LVADs were developed: "a new life, " "self-care, " and "resilience"; in addition, a crosscutting theme was identified: "support system." This article focuses on the theme "a new life, " described as a continuum of events. Individuals with advanced heart failure struggle with symptom burden and consider the implantation of the device as the final option to delay death; then, they wait for the surgery that represents a turning point, after which they begin to recover through a process of adjustment until they reach a new normality. Conclusions: Living with a retro-auricular LVAD impacts every aspect of people's lives. Knowing their experiences can help clinicians to develop targeted interventions and offer tailored support.